The Social Life of Anti-Terrorism Laws The War on Terror and the Classifications of the »Dangerous Other« - Eckert, Julia M. (Sozialtheorie, 2008)
This book addresses two developments in the conceptualisation of citizenship that arise from the »war on terror«, namely the re-culturalisation of membership in a polity and the re-moralisation of access to rights. Taking an anthropological perspective, it traces the ways in which the trans-nationalisation of the »war on terror« has affected notions of »the dangerous other« in different political and social contexts, asking what changes in the ideas of the state and of the nation have been promoted by the emerging culture of security, and how these changes affect practices of citizenship and societal group relations.